Florida Reclaimed Phosphate Mine Soils: Characteristics, Potential Uses, and Management Considerations - M. Wilson; Edward A. Hanlon (EDIS)
A critical nutrient for plant growth, phosphate helps sustain the world’s growing population. In 2010, seven mines in Florida produced approximately 10% of the world’s phosphate supply and more than 65% of the phosphate for the United States. But each year in Florida thousands of acres disturbed by strip-mining for phosphate rock must be reclaimed for other productive uses. This 11-page fact sheet provides a general characterization of the various soil types resulting from phosphate mine reclamation. Written by M. Wilson and E.A. Hanlon, and published by the UF Department of Soil and Water Science, October 2012.